2020
DOI: 10.1021/acs.jafc.0c01706
|View full text |Cite
|
Sign up to set email alerts
|

Pathway Engineering for Phenethylamine Production in Escherichia coli

Abstract: In this study, the metabolic pathway of phenethylamine synthesis was reconstructed by chromosomal integration and overexpression of the Enterococcus faecium pdc gene encoding phenylalanine decarboxylase in Escherichia coli. The genes encoding 3deoxy-D-arabinoheptulosonate-7-phosphate synthase (aroG), shikimate kinase II (aroL), chorismate mutase/prephenate dehydratase (pheA), and tyrosine aminotransferase (tyrB) in the phenethylamine synthetic pathway were sequentially chromosomally overexpressed. The phosphot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
4
4
Order By: Relevance
“…As depicted in Figure 5b, the maximum phenethylamine production of 555 ± 50 mg/L was achieved by strain PEA3.0 after 72 h, which was increased by 2.28‐fold compared with that of strain PEA1.0 (169 ± 20 mg/L). The phenethylamine level achieved in the shake flask by our study was 1.2 times higher than that of a recent report (Xu & Zhang, 2020). In addition, we found that both strain PEA1.0 and PEA3.0 gave a similar growth profile (Figure 5b).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…As depicted in Figure 5b, the maximum phenethylamine production of 555 ± 50 mg/L was achieved by strain PEA3.0 after 72 h, which was increased by 2.28‐fold compared with that of strain PEA1.0 (169 ± 20 mg/L). The phenethylamine level achieved in the shake flask by our study was 1.2 times higher than that of a recent report (Xu & Zhang, 2020). In addition, we found that both strain PEA1.0 and PEA3.0 gave a similar growth profile (Figure 5b).…”
Section: Resultscontrasting
confidence: 78%
“…Heterologous expression of tyrosinase and decarboxylase in the L‐tyrosine overproducing E. coli achieved 260 mg/L dopamine (Nakagawa et al, 2011). The metabolic pathway for the production of phenethylamine in E. coli was rebuilt using chromosomal integration of the phenethylamine synthesis pathway and the PP pathway, and the engineered strain produced 460 mg/L of phenylethylamine in a shake flask and 38.82 g/L in fed‐batch fermentation (Xu & Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…5b, the maximum phenethylamine production of 555±50 mg/L was achieved by strain PEA3.0 after 72 h, which was increased by 2.28-fold compared with that of strain PEA1.0 (169±20 mg/L). The phenethylamine level achieved in the shake flask by our study was also much higher than that of a recent report (Xu and Zhang 2020). In addition, we found that both strain PEA1.0 and PEA3.0 gave a similar growth profile (Fig.…”
Section: Resultscontrasting
confidence: 73%
“…Finally, 1.965±0.205 g/L tyramine, 703±21 mg/L dopamine, and 555±50 mg/L phenethylamine were obtained from 40 g/L glycerol in shake flask cultivation. The titers achieved by us were much higher than previous reports under shake flask conditions (Koma et al 2012; Nakagawa et al 2011; Xu and Zhang 2020).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation